Central nervous system cavernous malformations: cross‐sectional study assessing rebleeding risk after a second haemorrhage. (13th October 2022) - Santos, Alejandro N.; Rauschenbach, Laurèl; Gull, Hanah Hadice; Olbrich, Angelina; Lahl, Kirstin; Darkwah Oppong, Marvin; Dinger, Thiemo F.; Rieß, Christoph; Chen, Bixia; Lenkeit, Annika; Schmidt, Börge; Li, Yan; et al.
Abstract: Background and purpose: The purpose of this study was to investigate the 5‐year risk of a third bleeding event in cavernous malformations (CMs) of the central nervous system. Methods: Patients with cerebral or spinal CMs treated between 2003 and 2021 were screened using our institutional database. Patients with a complete magnetic resonance imaging dataset, clinical baseline characteristics, and history of two bleeding events were included. Patients who underwent surgical CM removal were excluded. Neurological functional status was obtained using the modified Rankin Scale score at the second and third bleeding. Kaplan–Meier and Cox regression analyses were performed to determine the cumulative 5‐year risk for a third haemorrhage. Results: Forty‐two patients were included. Cox regression analysis adjusted for age and sex did not identify risk factors for a third haemorrhage. 37% of patients experienced neurological deterioration after the third haemorrhage ( p  = 0.019). The cumulative 5‐year risk of a third bleeding was 66.7% (95% confidence interval [CI] 50.4%–80%) for the whole cohort, 65.9% (95% CI 49.3%–79.5%) for patients with bleeding at initial diagnosis, 72.7% (95% CI 39.3%–92.7%) for patients with a developmental venous anomaly, 76.9% (95% CI 55.9%–90.3%) for patients with CM localization to the brainstem and 75% (95% CI 50.6%–90.4%) for patients suffering from familial CM disease. Conclusions: During an untreated 5‐year follow‐up after a second haemorrhage, a significantly increased risk of a third haemorrhage compared to the known risk of a first and second bleeding event was identified. The third bleeding was significantly associated with neurological deterioration. These findings may justify a surgical treatment after a second bleeding event. Abstract : During an untreated 5‐year follow‐up after second hemorrhage, we identified a significantly increased risk of a third hemorrhage compared to the known risk of a first and second bleeding event. This risk was stratified according to different characteristics. Third bleeding was significantly associated with neurological deterioration.